UPAYA MENINGKATKAN KOMPETENSI GURU DALAM TEKNIK PENGOLAHAN DATA PENELITIAN - Neng Murialti; Dwi Widiarsih; Ranti Darwin; Muhammad Hidayat; M.Fikry Hadi; Mizan Asnawi (LPPM UMRI, 2019)
Higher Education other than as an educational institution that has the main task of carrying out the process of education and teaching, also has other tasks namely carrying out research and community service. Quality improvement of human resources of a nation means encouraging the improvement of the quality of the nation itself so that it has the ability to compete with countries in the world. The education world is one of the spearheads in the effort to improve the quality of human resources. So improving the quality of human resources must be supported by improving the quality of educators (teachers), because qualified teachers will be able to produce students who are also qualified. Efforts to improve the quality of human resources can be implemented jointly in the world of education. Lecturer of Development Economics Study Program Faculty of Economics and Business UMRI tries to help increase teacher competency in Pekanbaru City PGRI Vocational School, through training in the use of SPSS software as a teacher data processing research tool. After conducting data processing training with SPSS software, it is expected that the teacher assemblies can produce quality research to support education and teaching activities at Vocational High School level. Keywords: SPSS, Increased Teacher Competency, improving the quality of HR.